การศึกษาสภาพการบริหารโรงเรียนคุณธรรมชั้นนำในภาคตะวันออก สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - แก้วตา พึ่งตนเอง (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The objective of this research was to study the state of school administration of leading moral schools under the Office of the Basic Education Commission in the eastern region using the framework of PDCA (Deming Cycle) to administer the leading moral schools based on three aspects: cultivate moral: self development moral, work moral and society coexistence moral, good governance for administration and Sufficiency economy with moral. This research using questionnaires with checklist and rating scale for 258 informants comprising 86 administrators 86 project directors and 86 instructors from leading moral schools in the eastern region provinces Chon Buri, Rayong, Chantaburi and Trad. The data were analyzed using percentage, mean and standard deviation. The research findings were summarized as follows: The results of the study revealed that the practice on the PDCA cycle to administer the leading moral schools as a whole, was rated at the highest level. Considering each aspect, it was found that the maximum mean fell on D-Do, followed by P-Plan, and the lowest mean on C-Check.